(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Developing economies face a dual challenge of rapidly increasing transportation demand and the urgent need to decarbonize energy systems. While renewable energy deployment is accelerating globally, the intermittent nature of solar and wind generation presents significant challenges for grid stability and reliability. Simultaneously, transportation sectors remain heavily dependent on fossil fuels, contributing substantially to greenhouse gas emissions. This paper proposes a sector-coupled energy infrastructure framework that integrates renewable hydrogen production, electric mobility systems, and smart grid technologies to enhance grid flexibility and accelerate the transition toward net-zero transportation in developing economies. The framework leverages surplus renewable electricity for hydrogen production through electrolysis while utilising electric vehicles (EVs) as distributed energy storage resources through vehicle-to-grid (V2G) technologies. By coupling power, transportation, and hydrogen sectors, the proposed model addresses renewable energy curtailment, grid balancing, energy security, and transportation decarbonisation simultaneously. The study examines technological pathways, infrastructure requirements, policy mechanisms, and economic considerations for implementation. The proposed framework demonstrates how integrated hydrogen-electric mobility systems may improve renewable energy utilisation, reduce grid congestion, enhance system resilience, and support sustainable economic development through coordinated sector coupling between power, transport, and hydrogen systems. The paper concludes by outlining strategic recommendations for policymakers and stakeholders seeking to establish flexible, low-carbon transportation and energy infrastructures in developing economies.